Methodological bases of differentiated control and evaluation of special physical and functional fitness of swimmers at different stages of long-term sports training - Solopov, I. N.; Avdienko, V. B.; Fomichenko, T. G.; Bgantseva, I. V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to substantiate the main provisions of the method of differentiated control and evaluation of the special physical and functional fitness of swimmers at the stages of sports training.